Clinical Experience With Pharmacological Venous Thromboembolism Prophylaxis in the Underweight and Critically Ill. (October 2016) - Carter, Christopher; Bushwitz, Jennifer; Gowan, Mollie; Pope, Hannah; Human, Theresa; Gibson, Gabrielle; Owen, Emily; Hampton, Nick; Whitman, Craig
Background: The optimal regimen for pharmacological prophylaxis of venous thromboembolism (VTE) in underweight, critically ill patients is unknown.Objective: To describe prescribing patterns for VTE prophylaxis in underweight (≤50 kg or body mass index ≤18.5 kg/m 2 ), critically ill patients and identify the prevalence of VTE and bleeding.Methods: This was a retrospective cohort study that included patients who received standard- or reduced-dose VTE prophylaxis for ≥48 hours.Results: A total of 295 individuals were included in the study. The majority of underweight patients in this study (79.7%) received unfractionated heparin, 5000 units 3 times daily. No statistically significant difference in the prevalence of clinically relevant VTEs between the reduced- and standard-dose groups was observed (4.4% vs 5.6%, P = 1.00), but a higher proportion of bleeding events was identified within the standard-dose group (6.7% vs 11.2%, P = 0.4).Conclusions: Empirical dose reductions of VTE prophylaxis are infrequently used in underweight, critically ill patients. Further studies need to be conducted that assess the safety and efficacy of reduced-dose VTE prophylactic regimens in this population to determine if acceptable efficacy can be achieved, with lower risks of bleeding.